Analisis SWOT dengan Pendekatan Fuzzy Untuk Pemilihan Strategi Promosi Ekowisata Bukit Liang Bangkai di Kabupaten Tanah Bumbu - Oni Soesanto; Nursalam Nursalam; Tanto Budi Susilo; Ketut Mega Fortuna (Lambung Mangkurat University Press, 2019)
One of the potential of ecotourism in South Kalimantan that has not been much explored is the Liang Bangkai site in Tanah Bumbu. Ecotourism on the Liang Bangkai site highlights conservation in its cultural aspects and natural authenticity, without ignoring the economic aspects that are indicated to be unique and of high value. The artifact findings on this site are far more complete than the Sakulirang site, a site recommended by UNESCO as a world heritage (Sugiyanto, B., 2010). It is not easy for local governments to determine the right strategy in tourism promotion. This is related to many factors, one of which is the carefulness and thoroughness of the local government as decision makers in determining the criteria that are the strengths, weaknesses, opportunities and threats of each tourist location. Accuracy of the local government in digging information on each criterion built both externally and internally, then analyzed so that it can provide accurate information related to tourist sites and be able to formulate appropriate and measurable decision strategies for the promotion of ecotourism. The Fuzzy Analytical Network Process - Extend Analysis Chang method is used in determining the weight of interest between criteria and sub criteria and the weight of interest between promotion strategies. Based on the perception of the importance level of the sub-criteria for promotion strategies, the level of importance was found, namely Strengts - Opportunies (21.70%), Weakness - Opportunities (34.52%), Strengt - Threats (32.54%) and Weakness - Threats (11.24%). From these results, it can be seen that decision makers still emphasize strategies to overcome internal weaknesses to capture opportunities from potential Liang Bangkai sites and utilize the potential strength of the site to overcome external threats to the site.